Women political leadership in India : some important dimensions - Kumari, Archana; UGC National Seminar on "Dimensions of Women Political Leadership" (2009 : R. N. College, Hajipur); Archana Kumari; Verma, R. K., 1956-; Raj Narain College, Hajipur (New Delhi : Serials Publications, 2010)
Contributed articles presented at the National Seminar on "Dimensions of Women Political Leadership", held at R.N. College, Hajipur during 24-25 February 2009.
Includes bibliographical references (p. [418]-427).
English and Hindi.
Keywords: Women -- Government policy -- India -- Congresses; Panchayat -- India -- Congresses